Description of The Mathematical Logical Thinking Abilities of Students with Special Needs - Cholifah, Alifia Nur; Pradipta, Trisna Roy (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to describe the mathematical logical thinking abilities of students with special needs. This was a qualitative study that followed a case study design. The research subjects were selected using purposive sampling. The source of data in the study were 12th grade high school students, a total of 5 students with special needs (hearing impaired). This research was conducted in one of the schools in Jakarta. Data collection was done by administering a mathematical logical thinking ability test, conducting interviews, and categorizing students according to their level of mathematical logical thinking ability. The results of this study show that there are 2 students who have level 2 mathematical logical thinking ability. There is 1 student who has mathematical logical thinking ability level 1. There are 2 students with mathematical logical thinking ability level 0. Students with level 2 mathematical-logical thinking ability are able to fulfil all indicators of mathematical-logical thinking ability. Students with level 1 mathematical-logical thinking ability were able to fulfill three indicators of mathematical-logical thinking ability. Students with level 0 mathematical-logical thinking ability were unable to fulfill the indicators of mathematical-logical thinking ability.